Application of magnetic‑pulse treatment in electrode arc welding of AD1N alloy - K. V. Nikitin; S. S. Zhatkin; D. G. Chernikov; A. K. Skoroumov; D. A. Dunaev; V. A. Novikov (Литьë и металлургия, 2023)
The paper proposes and experimentally tests a new method of welding aluminum alloys with simultaneous magnetic‑pulse treatment (MPT) of the liquid and solidifying metal of the welding pool. The results of investigations on semi‑automatic welding of AD1N aluminum alloy with MPT of the molten pool are presented. The influence of welding and magnetic‑pulse treatment modes on the structure and physico‑mechanical properties of the weld zones is investigated. The research data is presented in the range of discharge energy variation from 250 to 500 J and pulse numbers from 23–24. The results show that the influence of the pulsed magnetic field with discharge energy of 350 and 500 J leads to an increase in material hardness. It is shown that welding with simultaneous MPT in these modes results in structure refinement and the formation of a textured zone with elongated grains at the border with the heat‑affected zone.